Analisis Peningkatan Kinerja Pegawai Sekretariat Daerah Kabupaten Bintan Dalam Upaya Mewujudkan Tata Kelola Pemerintahan Yang Baik (Good Governance) - Lestari, Puji; Indrawan, Muhamad Gita; Friadi, John; Wibisono, Chablullah; Satriawan, Bambang; Ngaliman, Ngaliman (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This research aims to analyze the influence of leadership style, work discipline and HR competency on the performance of Bintan Regency Regional Secretariat employees with job satisfaction as mediation. Results/findings: The results of the study showed that there was a significant and positive influence between the leadership style, work discipline on job satisfaction and employee performance. Meanwhile, competence does not affect job satisfaction but affects employee performance. Job satisfaction cannot moderate the influence of leadership style and HR competence on employee performance, but it can moderate work discipline on employee performance.